Utilizing appropriate technology for enhancing production and digital marketing of traditional food through a website - Muhamad Azrino Gustalika; Aditya Wijayanto; Riri Irma Suryani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Serayu Larangan Village in Purbalingga has MSMEs in the form of typical food, namely Jenang and Wajik "Jati Rasa". This MSME was founded during the Covid 19 pandemic. This MSME had problems in production and marketing. So far they have only used manual methods both in Jenang production and in sales. This service aims to help these MSMEs in increasing Jenang production and product marketing. The method used is a prototype for making tools to increase Jenang production and digital marketing to find out how important digital marketing is using a website for MSMEs to increase product marketing. The results achieved in this service are that participants can use automatic Jenang processing machines and coconut presses well and the electricity used is only 1 PS or the equivalent of 735 watts, and by using digital marketing with a website they can increase marketing globally and can be accessed anywhere and make sales effective and efficient from manual to automatic.